A Discussion of John Keats’s Ode to a Nightingale - Khadka, Kul Bahadur (Interdisciplinary Journal of Management and Social Sciences, 2021)
John Keats passes away at an early age but leaves many outstanding works behind. In his Ode to a Nightingale, the poet sees suffering on the earth and highly appreciates a nightingale’s marvelous music. This article discusses the pain-pleasure contrast and association in terms of the poet and the nightingale. It also explores the use of time and space in the poem. It is important to know where and when the bird is singing and the poet is sitting, listening to the bird’s music. The use of imagery ad symbols in the poem is very significant to connect the poet’s world with that of the bird. Art, death and life can be drawn as major themes in the poem. In order to strengthen the discussion, various books and critics’ opinions concerning Keats, the respective poem and Romanticism have been consulted. The discussion reveals the poet’s ugly and painful world which is real and the nightingale’s beautiful and pleasurable world which is ideal. The real contrasts from the ideal and sometimes they get associated with each other. In exclusion of the ideal, the real suffers and gets confused.